2009
DOI: 10.1002/app.29746
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and properties of cellulose/chitin blend filaments

Abstract: The focus of this article is the preparation and characterization of cellulose/chitin blend filaments obtained from cellulose/chitin xanthate blend solution over the experimental blend ratio, i.e., 2.89% and 6.46% (w/w) chitin content. The addition of chitin xanthate into cellulose xanthate leads to an increase of intermittence rate and the blend solution has good filtering property. Scanning electronic microscope photos shows that there exist grooves on the filaments surface, which are becoming coarse with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Chitosan is a natural polyaminosaccharide, and it has a repeating structural unit of 2‐acetamido‐2‐deoxy‐β‐ d ‐glucopyranose . Because of its nontoxicity, biodegradability, and biocompatibility, a range of biological applications have been reported for chitosan, including antibacterial fibrous membranes, tissue engineering for cell cultures, sorbents, and drug delivery . However, chitosan has shown some limitations because of its poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a natural polyaminosaccharide, and it has a repeating structural unit of 2‐acetamido‐2‐deoxy‐β‐ d ‐glucopyranose . Because of its nontoxicity, biodegradability, and biocompatibility, a range of biological applications have been reported for chitosan, including antibacterial fibrous membranes, tissue engineering for cell cultures, sorbents, and drug delivery . However, chitosan has shown some limitations because of its poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of hydrogen bonds in the blends is an important aspect of miscibility. Blending chitin with other polymers is an interesting way of preparing functional polymeric composites, such as hybrid scaffolds composed of chitin and collagen, or silk fibroin [19][20][21], blend fibers (filaments), beads, gels and membranes of cellulose and chitin [22][23][24][25][26], which indicated that good miscibility existed between chitin and some biopolymers. Alginate is a marine biopolymer, which is a binary linear hetero polysaccharide containing one, four-linked ˛-l-guluronic acid and ˇ-d-mannuronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan was in the form of microparticles in the above fibers and the difficulties during the manufacture are concerned with aggregation of microcrystalline chitosan particles or solid particles, blocking of filtration fabrics or spinnerets and inhomogenity distribution in the fiber structure, which all affect the fiber properties and behaviors. To make the distribution more homogeneous, chitosan, microcrystalline chitosan or chitin was xanthated by the reaction with carbon disulfide and blend with viscose dope (He, Ma, & Sun, 2009;Pang, He, & Wang, 2003;Yoshikawa et al, 1998). In this method, the spinning dope is easily homogenized.…”
Section: Introductionmentioning
confidence: 99%